A qualitative investigation into the perceived therapeutic benefits and barriers of a surf therapy intervention for youth mental health. (June 2021) - Drake, Cameron J.; Keith, Michael; Dober, Madeleine R.; Evans, Subhadra; Olive, Lisa S.
Highlights: Four therapeutic pathways linking surf therapy and mental health were identified. Three barriers to engagement in a surf therapy program were identified. Surf therapy may be an effective method to address youth mental health problems. Abstract: Objective: This study aims to investigate potential therapeutic pathways and barriers to participation in a surf therapy program for youth at risk of mental health problems from the perspective of participants, surf mentors and program coordinator. Method: Nineteen individuals, consisting of youth (n = 9, 5 male, 4 female, M = 12.8, SD = 2.6), mentors (n = 9, male 5, female 4, M = 37.60, SD = 13.62) and the Ocean Mind program coordinator (n = 1, male, age 26 years), participated in semi-structured focus groups or follow-up interviews. This qualitative study analysed data using inductive thematic analysis. Results: Six themes were identified in total, with self-efficacy, interpersonal skills and forming a mentorship being potential therapeutic pathways of the surf therapy intervention. Surf instruction techniques and family engagement were both identified as potential barriers that negatively affect participant engagement. Additionally, the natural environment was identified as both a potential therapeutic pathway and a barrier. Conclusion: Surf therapy interventions appears to hold a number of benefits for youth mental health via pathways relating to the promotion of mental health protective factors.